UPAYA GURU PAI DALAM MENGEMBANGKAN KREATIVITAS SISWA PADA MATA PELAJARAN PAI KELAS XI SMAN 1 KABUPATEN BENGKULU TENGAH - Leni Hartati (Al-Bahtsu : Jurnal Penelitian Pendidikan Islam, 2016)
This study in the background backs by the reality of a teacher doing teaching only the obligations and duties aseducators, do not have the skill and professionalism in carrying out his duties as a teacher, to further enhance students’creativity, so as to achieve the goals, whether the purpose of National Education and school goals.The problem in thisresearch is how the efforts of teachers in developing students’ creativity on the subjects of PAI class XI SMA N 1 CentralBengkulu Regency.There are two objectives in this study are: (1) Generate methods, ways, ideas, as well as efforts indeveloping the creativity of the students so that learning situation is more lively and fun. (2) .Increase effectiveness ofstudents so that student achievement can be improved. The method used is descriptive qualitative method.The results ofthis study explains that the development of student creativity on the subjects of PAI in SMA N 1 Central Bengkulu district,using the method of lecture, discussion, question and answer, tasks, and demonstrations. The media used is wifi, infokus,power point and sculpture. While the model used by teachers PAI is a jigsaw learning, the power of two, and practice.Theschool environment is very supportive of teachers PAI study of creativity by providing complete facilities and infrastructure.The skills of the students covering the skills to read the Qur’an properly, hosted, calligraphy and decoration itself in themosque, and conduct other religious activities.It is evident from the observation of the level of creativity of students beincreased after the efforts made by teachers PAI, using methods, media, and practice some learning model, so the levelof creativity of students is much more increased.